The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jdent.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ozone on progression or regression of artificial caries-like enamel lesions in vitro

Abstract: Ozone therapy combines the use of ozone gas and adjunct products called Reductant and the patient kit, which all contain fluoride. This study investigated the effect of between all the three regimes tested and the control with a trend favouring Ozone/Reductant/Patient Kit group. In our model, it appeared that Ozone treatment alone is not effective in protecting the enamel against demineralisation or promoting remineralisation, unless combined with the reductant/patient kit, which contain high levels of fluorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(15 reference statements)
0
3
1
1
Order By: Relevance
“…The results of our study are in agreement with the observations by Samuel et al 41 , who showed that ozone significantly improved the remineralizing capability of nano-hydroxyapatite on artificially induced enamel caries lesions compared to nano-hydroxyapatite alone. Results contrary to the present study were reported by Tahmassebi et al 42 , who analysed in vitro the effect of ozone on artificial caries-like lesions and concluded that ozone alone is not effective in promoting remineralization or preventing enamel demineralization unless combined with an agent containing high levels of fluoride. The diverse observations may result from a different way of ozone application and a different ozone generator.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of our study are in agreement with the observations by Samuel et al 41 , who showed that ozone significantly improved the remineralizing capability of nano-hydroxyapatite on artificially induced enamel caries lesions compared to nano-hydroxyapatite alone. Results contrary to the present study were reported by Tahmassebi et al 42 , who analysed in vitro the effect of ozone on artificial caries-like lesions and concluded that ozone alone is not effective in promoting remineralization or preventing enamel demineralization unless combined with an agent containing high levels of fluoride. The diverse observations may result from a different way of ozone application and a different ozone generator.…”
Section: Discussioncontrasting
confidence: 99%
“…An increase in the S. mutans and Lactobacillus counts, seen during orthodontic treatment, might affect the balance of the oral flora and produce a cariogenic disposition (19). Ozone, which is a strong antioxidant and antimicrobial, is reported to be one of the agents that can be used to suppress cariogenic oral flora in at-risk individuals (4,20). However, owing to its strong oxidizing effect, ozone might have a negative impact on resin tooth adhesion (13).…”
Section: Discussionmentioning
confidence: 99%
“…17711719.4.0000.5374) and stored in 0.1% thymol solution for a maximum of 6 months. 12 Written informed consent ( ) was obtained from the patients to provide the teeth for the experiment.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“… 11 In addition to its use as a medical antimicrobial and therapeutic agent, 11 its use in in-office bleaching techniques with agents with high concentrations of hydrogen peroxide, at 37.5% 7 and 38%, 8 9 10 has shown significant bleaching effects; additionally, it does not affect the mineral content of the enamel. 12 Furthermore, ozone bleaching has been shown to result in reduced dental sensitivity compared with the conventional in-office technique. 10…”
Section: Introductionmentioning
confidence: 99%